Musculoskeletal Problems in Patients With COVID-19: A Review Study - Monireh Motaqi; Boshra Hatef; Ahmadreza Askari Ashtiani; Ali Ghanjal (Journal of Modern Rehabilitation, 2021)
Introduction: SARS-CoV-2 is a coronavirus, primarily targets the human respiratory system and causes symptoms similar to those of pneumonia. However, these patients do not only experience respiratory problems. Those with COVID-19 infection may show various signs and symptoms, including fever, shortness of breath, dry cough, nasal congestion, sore throat, nausea, vomiting, myalgia, arthralgia, fatigue (muscular and mental), joint swelling, headache, diarrhea, as well as some musculoskeletal symptoms. Therefore, this article aimed to investigate the major musculoskeletal problems in patients with COVID-19 through a review study. Materials and Methods: This study gathered the related published studies in PubMed, Web of Science, and Science Direct. The main keywords were “COVID-19”, “coronavirus”, and “musculoskeletal problem”. Results: The major musculoskeletal symptoms include muscle fatigue, myalgia, arthralgia, joint swelling (reactive arthritis), and such conditions as joint limitations, tendon shortening, and muscle weakness due to prolonged bed rest. However, their prevalence rates have not been investigated systematically. Conclusion: Our findings revealed that attention to musculoskeletal rehabilitation of patients with COVID-19 is as essential as their respiratory rehabilitation. Besides, it would be effective in reducing the physical complications of hospitalization, returning to independence and functional activities, and improving the quality of the patients’ life.